Living Arrangements of Iranian Older Adults and Its Socio-demographic Correlates - Rasoul Sadeghi; Fatemeh Sadat Khodaparast (University of Social Welfare & Rehabilitation Sciences, 2023)
Objectives In the context of family changes and population aging, changing the pattern of life arrangements of older adults has become a social and policy issue. In this regard, this article aims to investigate the patterns of living arrangements of older adults and its socio-demographic correlates. Methods & Materials A secondary analysis of micro-census data for 2006 and 2016 was used. The study population include people aged 60 and over living in households. Multinomial logistic regression tests and SPSS26 were used to data analysis.  Results Living with a spouse and children is the dominant form of living arrangements for older adults in Iran. However, the share of this pattern has been almost stable in the decade 2006-2016, and in contrast, the share of older adults living alone has increased from 12% to 15%. The results indicated a significant gender difference in the pattern of living alone and its prevalence in elderly women (24.1%) was four times higher for older than older men (5.6%). Also, the results showed that with increasing age, the probability of living alone increases and with increasing the level of education of the older adults, the probability of living alone decreases. In addition, rural older adults are more likely to live alone than urban older adults. Conclusion Although living with a spouse and children is still the dominant pattern, the living alone of older adults is increasing. Women are more likely to live alone than older men and face more problems. Therefore, paying attention to the issues and problems of the alone elderly women should be the headline of the country's welfare programs and policies. In addition, by creating employment in rural areas, it is possible to prevent the migration of young people to the city to some extent and reduce the possibility of living alone among rural older adults.